THERMAL WORK OF HEATING FURNACES OF ROLLING MANUFACTURE. Message 4. EXPERIMENTAL RESEARCHES OF METAL HEATING IN ANNULAR FURNACES - V. I. Timoshpolsky; I. A. Trusova (Литьë и металлургия)
The results of experimental researches of thermal work at the example of the annular furnaces functioning in conditions of axis-rolling production of Dneprovsk metallurgical industrial complex named after Dzerzhinsky are given.